The Development of Copper Radiopharmaceuticals for Imaging and Therapy - Shokeen, Monica; J. Wadas, Thaddeus (Medicinal Chemistry, 2011)
The increasing use of positron emission tomography in preclinical and clinical settings has widened the demand for radiopharmaceuticals with high specificity that can image biological phenomena in vivo. While many PET tracers have been developed from small organic molecules labeled with carbon-11 or fluorine-18, the short half-lives of these radionuclides preclude their incorporation into radiotracers, which can be used to image biological processes that are not induced immediately after system perturbation. Additionally, the continuing development of targeted agents, such as antibodies and nanoparticles, which undergo extended circulation, require that radionuclides with half-lives that are complimentary to the biological half-lives of these molecules be developed. Copper radionuclides have received considerable attention since they offer a variety of half-lives and decay energies and because the coordination chemistry of cooper and its role in biology is well understood. However, in addition to the radiometal chelate, a successful copper based radiopharmaceutical depends upon the chemical structure of the entire radiotracer, which may include a biologically important molecule and a chemical linker that can be used to deliver the copper radionuclide to a specific target and modulate its in vivo properties, respectively. This review discusses the development of copper radiopharmaceuticals and the importance of factors such as chemical structure on their pharmacokinetics in vivo.
Keywords: Copper radionuclides